Advances in Mechanical and Electronic Engineering Volume 3 - Jin, David; Lin, Sally; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2013)
This book includes the volume 3 of the proceedings of the 2012 International Conference on Mechanical and Electronic Engineering(ICMEE2012), held at June 23-24,2012 in Hefei, China. The conference provided a rare opportunity to bring together worldwide researchers who are working in the fields. This volume 3 is focusing on Electronic Engineering and Electronic Communication; Electronic Engineering and Electronic Image Processing.
Keywords: Engineering; Mechanical engineering; Computer engineering; Engineering; Electrical Engineering; Mechanical Engineering